Computing the cosmos. - Hellemans, A. (IEEE spectrum)
This article describes an ambitious project which aims to simulate on a supercomputer the evolution of the entire universe from just after the Big Bang until the present. An international group of scientists, dubbed the Virgo Consortium, is creating the largest and most detailed computer model of the universe ever made. While other groups have simulated chunks of the cosmos, the Virgo simulation is going for the real thing. The cosmologists' best theories about the universe's matter distribution and galaxy formation becomes equations, numbers, variables, and other parameters in simulations running on one of Germany's most powerful supercomputers, an IBM Unix cluster at the Max Planck Society's Computing Center in Garching, near Munich.